Analisis Bibliometrik Layanan Bimbingan dan Konseling dengan Menggunakan Teknik SFBT - Wandari, Nadya Indria; Krinandini, Shindy (YASIN, 2025)
This study is motivated by the growing attention to the effectiveness of guidance and counseling services that apply the Solution-Focused Brief Therapy (SFBT) approach, as well as the need to map the development and research trends related to this approach in the context of education and mental health. The aim of this research is to analyze publication trends, keywords, and scientific collaboration in studies on SFBT using a bibliometric approach. The method employed is bibliometric analysis of articles published between 2010 and 2024, using VOSviewer software. The analysis results indicate a significant increase in the number of publications on SFBT, with dominant themes including school counseling, mental health, youth interventions, and the effectiveness of short-term therapy. Keyword clustering reveals strong interconnections among various research topics, indicating that the SFBT approach is developing consistently within academic and practical domains. The study concludes that SFBT is a theoretically grounded and practically applicable counseling approach across diverse contexts. The implications of this research provide a strategic foundation for academics, practitioners, and researchers to develop more focused research directions and expand the application of SFBT in professional guidance and counseling services.